FEMALE OPPRESSION TOWARD FEMALE CHARACTERS IN MARS NEED MOM MOVIE - Rahma, Azizatur; Sili, Surya; Wati, Erna (Fakultas Ilmu Budaya Universitas Mulawarman, 2017)
In this study the researcher analyzed the oppression from female character toward other female characters. The researcher only discussed two female characters, Milo’s mother and Gribble’s mother who gained the oppression from Supervisor as another female character because the researcher wanted to prove that oppression could also happen from female to female (same sex). There are two objectifies of the study in this research, to show the forms of oppression which occur toward female characters in Mars Need Mom movie and to analyze how the female characters, experience the oppression that are shaped by another female character in Mars Need Mom movie. The five faces of oppression is a theory that is explained by Irish Marion Young. The theory is related toward the form of oppression which usually occur in the society. This form of oppression somehow called as injustice action that adhere toward people or group because of several reasons, such as class, race and gender. The five faces of oppression are marginalization, exploitation, powerlessness, cultural imperialism and violence. The result of this study are, Milo’s mother got three faces oppression from Supervisor, those three oppression are marginalization, powerlessness and violence. Whereas Gribble’s mother got four faces oppression. The four faces of oppression are exploitation, marginalization, powerlessness, and violence. And the process of oppression that was gained by two mothers firstly which was done by Supervisor (female) was, Supervisor observed them, abducted them and extracted them using solar extraction machine. The different process from both of them is Martians succeed to extract Gribble’s mother, whereas Milo’s mother, the extraction is failed because Milo was successful in saving his mother.Based on those analysis, the researcher concludes that the oppression toward women can be done by women. Therefore, the researcher believes that the oppression toward women is not always caused by gender assumption that male is superior rather than women, but the oppression can be happened due to the power which is had by the perpetrators (men and women) of oppression. Key words: female, oppression, feminism, gender roles